2014
DOI: 10.3390/w6092575
|View full text |Cite
|
Sign up to set email alerts
|

Effect of P-Reactive Drainage Aggregates on Green Roof Runoff Quality

Abstract: Abstract:The main hypothesis of the presented study is that the negative effect of phosphorus leaching from a green roof substrate can be reduced by including P-reactive material in a drainage layer. In this work, different aggregates (Pollytag ® , lightweight expanded clay aggregates, chalcedony, serpentynite and crushed autoclaved aerated concrete) to be used as the green roof drainage layer are described. Physical parameters, e.g., granulometric composition, water absorption, bulk density and porosity are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…Only in the case of one of tested material-crushed limestone-P was not detected in water and hydrochloric acid extracts. The pH of material is high, what is typical for materials containing Ca, but it also creates a potential for being reactive for P leaching from other substrate components [59][60][61]. Gravel, sand, volcanic rock, and expanded clay were not the source of easily dissolved P, however they contain P than can contaminate the runoff in specific conditions (Table 3).…”
Section: Potential P Leachingmentioning
confidence: 99%
“…Only in the case of one of tested material-crushed limestone-P was not detected in water and hydrochloric acid extracts. The pH of material is high, what is typical for materials containing Ca, but it also creates a potential for being reactive for P leaching from other substrate components [59][60][61]. Gravel, sand, volcanic rock, and expanded clay were not the source of easily dissolved P, however they contain P than can contaminate the runoff in specific conditions (Table 3).…”
Section: Potential P Leachingmentioning
confidence: 99%
“…The accumulation of P leads to changes in terrestrial, aquatic and marine ecosystems, by eutrophication and ocean anoxic events; both processes are associated with loss of biodiversity and thus a reduction of natural resilience [1,[4][5][6]. According to Karczmarczyk et al [6], 1 g of P released into water bodies promotes the growth of up to 100 g of algae, enhancing eutrophication of surface water. Modelling analysis performed by Rockström et al [1] has shown that P inflow into oceans will increase 10 times in the next 1000 years, leading to extreme anoxic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…NBS promote an efficient use of natural resources, human well-being and a socially inclusive green growth by replicating natural process and integrating ecosystem services into the human environment [7][8][9]. Several authors have demonstrated that NBS, such as constructed wetlands (CWs) and biological filter beds are environmentally friendly and efficient at removing P from water [5,6,[10][11][12]. In such systems, the filter medium plays an important role at recovering P, mainly by promoting absorption and precipitation processes [5,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The primary functions of a drainage layer are to remove excess rain water but still retain some amount of water, while being light and thin. Recent studies have focused on the optimization of the drainage layer for the removal of nutrients released from the growing medium of a green roof during rainfall events [2]. On the other hand, the hydraulic behaviour of a green roof is strongly influenced by the characteristics of the growing medium, which must be highly permeable, in order to avoid ponding of water on the GR surface.…”
Section: Introductionmentioning
confidence: 99%